SEDIMENT ANALYSIS OF THE ABUNDANCE AND TYPES OF MACROZOOBENTHOS IN THE CITUMANG RIVER PANGANDARAN REGENCY WEST JAVA PROVICE - Shevina, Stania
Apart from being used as a tourist attraction, there is also an input of domestic waste along the Citumang River. Hence, this river requires water quality monitoring. One of the parameters commonly used is macrozoobenthos. An analysis was carried out regarding the organic matter content of sediment, the distribution of sediment particles, and the abundance of macrozoobenthos. This research aims to determine the relationship between sediment and the abundance of macrozoobenthos. The results of sediment texture analysis at point SP 1 are dominated by gravel, SP 2, 3, and 5 are dominated by sand, and at points SP 4 and 5 the distribution of particles is quite even. The results of the highest organic matter content in sediment were found at point SP 4, and the highest abundance of macrozoobenthos was also found at point SP 4. After carrying out a correlation test, the results showed that macrozoobenthos diversity was strongly negatively correlated with the parameters of total organic carbon and total nitrogen. On the other hand, macrozoobenthos abundance was strongly positively correlated with total organic carbon, total nitrogen, and percentage of silt and clay. Furthermore, macrozoobenthos diversity is very strongly positively correlated with phosphate.